Psychiatric Research in Nepal - Sharma, P.; Subedi, S. (Journal of Psychiatrists' Association of Nepal, 2019)
The Global Burden of Disease study ranks mental disorders and substance use disorders as the fifth-placed group based on global burden and ranks them first based on years living with disability. There is a gross imbalance between the burden of disease and mental health resources especially in low and middle income countries (LMICs). Research in this field can and should play a substantial role in improving these situations.